Physiological and comparative proteomic characterization of Desulfolithobacter dissulfuricans gen. nov., sp. nov., a novel mesophilic, sulfur-disproportionating chemolithoautotroph from a deep-sea hydrothermal vent - Hashimoto, Yurina; Shimamura, Shigeru; Tame, Akihiro; Sawayama, Shigeki; Miyazaki, Junichi; Takai, Ken; Nakagawa, Satoshi (Frontiers in Microbiology, 2022)
In deep-sea hydrothermal environments, inorganic sulfur compounds are important energy substrates for sulfur-oxidizing, -reducing, and -disproportionating microorganisms. Among these, sulfur-disproportionating bacteria have been poorly understood in terms of ecophysiology and phylogenetic diversity. Here, we isolated and characterized a novel mesophilic, strictly chemolithoautotrophic, diazotrophic sulfur-disproportionating bacterium, designated strain GF1T, from a deep-sea hydrothermal vent chimney at the Suiyo Seamount in the Izu-Bonin Arc, Japan. Strain GF1T disproportionated elemental sulfur, thiosulfate, and tetrathionate in the presence of ferrihydrite. The isolate also grew by respiratory hydrogen oxidation coupled to sulfate reduction. Phylogenetic and physiological analyses support that strain GF1T represents the type strain of a new genus and species in the family Desulfobulbaceae, for which the name Desulfolithobacter dissulfuricans gen. nov. sp. nov. is proposed. Proteomic analysis revealed that proteins related to tetrathionate reductase were specifically and abundantly produced when grown via thiosulfate disproportionation. In addition, several proteins possibly involved in thiosulfate disproportionation, including those encoded by the YTD gene cluster, were also found. The overall findings pointed to a possible diversity of sulfur-disproportionating bacteria in hydrothermal systems and provided a refined picture of microbial sulfur disproportionation.